2008
DOI: 10.1002/14651858.cd004812.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions implemented through sporting organisations for increasing participation in sport

Abstract: There is an absence of high quality evidence to support interventions designed and delivered by sporting organisations to increase participation in sport. Interventions funded and conducted in this area must be linked to a rigorous evaluation strategy in order to examine overall effectiveness, socio-demographic differentials in participation and cost-effectiveness of these strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…However, there is no clear distinction between individual exercise and group exercise in such physical activity, and the determinants of participation in group exercise are unclear. A review on interventions implemented through sporting organizations to increase participation in sports showed that there is no high quality evidence of effective methods for increasing sports participation 41) . Among the very few studies conducted to clarify the determinants of participation in group exercise, one crosssectional study looked at adults in New York City 32) .…”
Section: Determinants Of Participation In Group Exercisementioning
confidence: 99%
“…However, there is no clear distinction between individual exercise and group exercise in such physical activity, and the determinants of participation in group exercise are unclear. A review on interventions implemented through sporting organizations to increase participation in sports showed that there is no high quality evidence of effective methods for increasing sports participation 41) . Among the very few studies conducted to clarify the determinants of participation in group exercise, one crosssectional study looked at adults in New York City 32) .…”
Section: Determinants Of Participation In Group Exercisementioning
confidence: 99%
“…Two of the included reviews were Cochrane reviews [12,13], which we found on 3 other sources: DoPHER, DARE, and PubMed. We retrospectively searched the Cochrane Database of Systematic Reviews using terms derived from our PubMed strategy, as both databases index research using the same MeSH.…”
Section: Strengths and Weaknesses Of This Analysismentioning
confidence: 99%
“…Improvements in the research in this area are desirable. Particularly, there is a need for controlled study designs, incorporating both the short- and longer-term effects of sporting programs and activities, to move towards providing evidence-based programs [27,28]. …”
Section: Introductionmentioning
confidence: 99%